FGF Signaling Pathway: A Key Regulator of Stem Cell Pluripotency - Mossahebi-Mohammadi, Majid; Quan, Meiyu; Zhang, Jin-San; Li, Xiaokun (Frontiers in Cell and Developmental Biology, 2020)
Pluripotent stem cells (PSCs) isolated in vitro from embryonic stem cells (ESCs), induced PSC (iPSC) and also post-implantation epiblast-derived stem cells (EpiSCs) are known for their two unique characteristics: the ability to give rise to all somatic lineages and the self-renewal capacity. Numerous intrinsic signaling pathways contribute to the maintenance of the pluripotency state of stem cells by tightly controlling key transcriptional regulators of stemness including Sox-2, Oct3/4, Klf-4, Nanog and c-Myc. Signaling by Fibroblast growth factor (FGF) is of critical importance in regulating stem cells pluripotency. The FGF family is comprised of 22 ligands that interact with four FGF receptors (FGFRs). FGF/FGFR signaling governs fundamental cellular processes such as cell survival, proliferation, migration, differentiation, embryonic development, organogenesis, tissue repair/regeneration, and metabolism. FGF signaling is mediated by the activation of RAS- MAPK, PI3K-AKT,PLCγ and STAT, which intersects and synergizes with other signaling pathways such as Wnt, Retinoic acid and TGF-β signaling. In the current review, we summarize the role of FGF signaling in the maintenance of pluripotency state of stem cells through regulation of key transcriptional factors.